2014
DOI: 10.1002/mrm.25506
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of the intravoxel incoherent motion threshold separating perfusion and diffusion effects: Proposal of a standardized algorithm

Abstract: IVIM parameters strongly depend upon the choice of the b-value threshold used for computation. The proposed algorithm may be used as a robust approach for IVIM analysis without organ-specific adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
108
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 36 publications
7
108
2
2
Order By: Relevance
“…Various fitting algorithms have been used to determine IVIM parameters, including asymptotic fitting (9)(10)(11)(12)(19)(20)(21)24,41,45,46,48,51,53), nonlinear least square (usually Levenberg-Marquardt) fitting (23,42,47,52,54,55), and Bayesian fitting (15,22,40,43,50). Current review cannot draw conclusion which one is better than others, nor can the mean values be compared (Figure 8).…”
Section: Image Post-processing Methods For Ivim Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Various fitting algorithms have been used to determine IVIM parameters, including asymptotic fitting (9)(10)(11)(12)(19)(20)(21)24,41,45,46,48,51,53), nonlinear least square (usually Levenberg-Marquardt) fitting (23,42,47,52,54,55), and Bayesian fitting (15,22,40,43,50). Current review cannot draw conclusion which one is better than others, nor can the mean values be compared (Figure 8).…”
Section: Image Post-processing Methods For Ivim Parametersmentioning
confidence: 99%
“…Accumulation of collagen deposits and activated stellate cells contribute to increased hepatic resistance to portal blood flow, development of portal hypertension, and reduced portal blood perfusion. The decrease of blood perfusion can arise from a number of concomitant alterations in the tissue microenvironment, including collagen deposition, fatty (9)(10)(11)15,23,24,42,43,45,46,(48)(49)(50)(51)(53)(54)(55), free-breathing (FB) (19)(20)(21)40,41,47), and breath-hold (BH) (44). Solid line represents the median value of each group.…”
Section: Ivim For Liver Fibrosis Evaluationmentioning
confidence: 99%
“…These differences are in part a consequence of the use of different acquisition or processing protocols, for example, the b ‐values used,9, 24 or of using different fitting algorithms 3, 25. However, there might also be physiological causes for this variability; for example, pseudodiffusion was found to correlate with perfusion in an electrocardiogram (ECG)‐triggered time‐resolved study of healthy kidneys,26 while IVIM‐derived parameters were also shown to be sensitive to diuretic challenges 27.…”
mentioning
confidence: 99%
“…Another fact adding to the instability of typically used algorithms to fit the whole IVIM model at once is the dependence of the fitting variables among each other. 3 To overcome this issue, different approaches have been used, including fixing of the pseudodiffusion coefficient, Bayesian fitting, and discretization of the fitting parameters. [4][5][6][7][8][9][10] One of the most commonly used approaches today is a multistep procedure calculating separately 1 IVIM parameter after the other, [11][12][13][14][15][16][17][18][19][20][21][22][23] thereby reducing the degree of freedom for each individual step.…”
mentioning
confidence: 99%
“…To eliminate the need of choosing such a b-value threshold, a parameterfree version of the very commonly used multistep procedure for the IVIM model was proposed recently. 3 In this study, we expanded the proposed parameter-free segmented algorithm for a combined IVIM-DKI model of diffusion and evaluated its performance and possible systematic differences in comparison with the simpler IVIM diffusion model.…”
mentioning
confidence: 99%